Pemanfaatan Media Gambar dalam Mengenalkan Tokoh Pahlawan Indonesia kepada Siswa SB Sungai Buloh Malaysia - Anggara, Bayu; Heriyana, Tio; Casnan; Hadiana, Oman; Astria Nur, Hana (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Education plays a crucial role in shaping understanding and attitudes, particularly regarding national values and patriotism. This community service activity aims to introduce Indonesian national heroes to students at Sanggar Guidance (SB) in Sungai Buloh, Malaysia, utilizing visual media as an effective teaching aid. Although access to formal education in non-formal environments abroad is often limited, the use of instructional materials such as illustrated posters can enhance students' interest and comprehension. The method employed is a qualitative descriptive approach involving documentation, interviews, and observation. The process consists of three stages: media preparation, interactive learning, and student reflection using hero figures. On December 1, 2023, a socialization session introducing national heroes through visual media was conducted for fourth-grade students at SB Sungai Buloh. The results were highly encouraging, as the students' average score increased from 45.00 to 95.00, reflecting a gain of 50 points or approximately 111.11%. Prior to this activity, students struggled to identify national heroes, and few posters of Indonesian figures were displayed on the walls. To address this, a media-based learning approach was implemented, enabling students to learn visually. The activity demonstrated that visual media fostered greater enthusiasm, engagement, and comprehension of core values such as courage. In addition, the program facilitated mentor access and demonstrated potential as a relevant and contextual alternative teaching method to strengthen the identity of the younger generation abroad.